NASH-related Hepatocellular carcinoma: current therapeutic approaches and the emerging role of sodium homeostasis as a novel targeting strategy - Ashkar, Abdulsalam; Fiorilla, Simone; Tasso, Francesco; Carini, Rita (Frontiers in Pharmacology, 2025)
Non-Alcoholic Steatohepatitis (NASH) rates are progressively accelerating due to lifestyle changes, which contribute to increased Hepatocellular carcinoma (HCC) incidence. HCC accounts for 90% of liver cancer cases, which ranks as the sixth prevalent, and the third leading cause of cancer-related deaths globally. NASH-HCC outweighs the decline in viral hepatitis-HCC, leaving a gap in the available therapies. The limited overall survival in the current treatments invokes the necessity of exploring novel therapeutic strategies to improve the poor prognosis of HCC. The pH gradient is a hallmark of cancer and is associated with increased intracellular sodium. Elevating this accumulation of intracellular sodium with sodium ionophores, such as Monensin, leads to selective death of murine HCC cancer cells without affecting the functionality of vital organs and proliferating activity of normal and transformed tissues. This study synthesizes the status of HCC risk and management, its molecular landscape, and sheds light on exploiting the elevated accumulation of intracellular sodium as a novel therapeutic strategy against HCC.